Greater Mekong Subregion COVID 19 response and recovery plan 2021 to 2023. (Regional cooperation strategy and programs., 2021)
The focus is on human and animal health to prevent the spread of diseases along with additional support for vulnerable and returning migrants and assistance in reestablishing economic activities. It represents a project implementation mechanism for the Greater Mekong Subregion Economic Cooperation Program Strategic Framework 2030.